PENGARUH KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI BADAN PERTANAHAN NASIONAL (BPN) KABUPATEN BOYOLALI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Gustian Diah Wardani; Adi Susanto; Yulis Maulida Berniz (CV. Amerta Media, 2022)
This study aims to analyze the influence of communication and work environment on employee performance with job satisfaction as a mediating variable. This research was carried out on employees of the National Land Agency (BPN) of Boyolali Regency. This study usedprimary data obtained by distributing questions to respondents and through literature studies. The sample in this study were 87 respondents with sampling technique, namely simple random sampling. Data analysis used is multiple regression analysis with the help of SPSS v.16. The results of this study indicate that communication has a positive effect on employee performance, the work environment has a positive effect on employee performance, communication has a positive effect on job satisfaction, the work environment has a positive effect on job satisfaction, job satisfaction has a positive effect on employee performance. While the results of the mediation test indicate that job satisfaction mediates the influence of communication and the work environment on employee performance. Keywords: communication, work environment, employee performance, job satisfaction